KARAKTERISTIK USAHA PERIKANAN TANGKAP MINI PURSE SEINE YANG BERPANGKALAN DI PPI KARANGANYAR KABUPATEN REMBANG - Dian Wijayanto; Faik Kurohman (Fakultas Perikanan dan Ilmu Kelautan UNDIP, 2018)
Fish Landing Place of Karanganyar is one of the centers of fishing activities in Rembang Regency with the dominant fishing gear is mini purse seine. Information about the characteristics of fisheries is important for the development planning of fisheries. This research purpose was to analysis the characteristics of mini purse seine fishing business based in PPI Karanganyar, both related to technical and financial aspects. Financial analysis used RC ratio. Primary data collection used convinience sampling to 30 respondents. The results showed that fishermen of mini purse seine use wooden vessels (10 to 30 GT), with a operation time of 1 week per trip. Peak season occurs in December to March, famine season occurs in August to November and regular season occurs in April to July. Fish target pf mini purse seine is the pelagic fish. The fishing ground is at WPP 712. Investment of vessel is IDR 500 million to IDR 600 million per unit, vessel engine of IDR 80 million to 100 million, supporting machine of IDR 20 million to IDR 30 million, and fishing gear of IDR 200 million to IDR 220 million. In the operation of mini purse seine, fuel procurement cost is about IDR 3.5 million to IDR 4 million per trip, consumption cost around IDR 1.5 million to Rp 2 million per trip, and ice procurement of IDR. 1.5 million to IDR 2 million per trip. RC ratio of mini purse seine business is about 2.43.Keywords: mini purse seine, RC ratio, PPI Karanganyar-Rembang